INCLUSIÓN EDUCATIVA Y SU IMPACTO EN EL DESARROLLO INTEGRAL EN EDUCACIÓN INICIAL II - LEDESMA SOLÓRZANO TANNIA KATHERINE (2024)
This thesis investigates how educational inclusion impacts the holistic development of children in Initial II at Unidad Educativa Réplica Eugenio Espejo, located in Babahoyo, Los Ríos Province. Despite the diversity among students, including varying abilities and cultural backgrounds, there is a noted lack of pedagogical strategies and adapted resources to meet each student's specific needs. This lack of attention to diversity can create barriers to learning and participation, affecting holistic development and the sense of belonging for children. The general objective of the research is to establish educational inclusion strategies and practices that promote the holistic development of children. Specific objectives include analyzing the importance of diversity and inclusion, identifying implemented diversity and inclusion programs, and determining the level of holistic development in relation to children's academic performance. The methodology includes participant observation, semi-structured interviews, and analysis of institutional documents. The research is expected to highlight the significance of inclusive education in the holistic development of children. As a potential conclusion, the promotion of inclusive educational strategies and practices is anticipated to have a positive effect on the holistic development of all children. It is expected that inclusive education will foster an environment where all children have the opportunity to actively participate in their learning, thereby contributing to their academic, emotional, and social growth.